Freeform 3D printing of polymers for biomedical applications - Chen, Shengyang (Nanyang Technological University, 2021)
Freeform three-dimensional (3D) printing is one of emerging 3D printing techniques, particularly, revolutionizing the field of additive manufacturing for biomedical applications. Many biomaterials including hydrogels have low self-supporting capability and poor mechanical stabilities during material processes; thus, their printability is often poor. A freeform 3D printing system consists of a supporting matrix for holding up the extruded ink during printing, allowing for the omnidirectional writing of the ink material while the soft printed filaments are slowly cured. This approach not only breaks the structure design restrictions of conventional layer-by-layer fabricating process, but also helps to realize 3D printing of innovative materials regardless of their printability. 3D freeform printing systems are classified into three main categories, positive freeform 3D printing, negative freeform 3D printing, and functional freeform 3D printing. Positive freeform 3D printing refers to the printing process of a curable ink in a removable supporting matrix. Similar to conventional extrusion 3D printing, the final product obtained from the whole process is the printed material or the ink. Negative freeform 3D printing is an opposite process from positive printing, in which the matrix will be the final product instead of the extruded ink. A fugitive or sacrificial ink is used to draw an internal pattern and will be finally removed to create hollow channels. The functional freeform 3D printing systems focus more on the functionalization of a printed material besides its printability through additional chemical reactions during printing. In this thesis, I mainly focus on two freeform 3D printing systems, positive and functional freeform 3D printing. Many medical-grade biomaterials including silicone rubber, poly (methyl methacrylate), and most hydrogels are not proper for 3D printing due to their low self-supportability and slow solidification processes. Thus, the positive 3D freeform 3D printing method can be applied to make those biomaterials printable through direct printing approaches. Also, biomaterials themselves sometimes show low bioactivity and poor mechanical stability under physiological conditions. Thus, through the functional freeform 3D printing system with or without cells, additional functionalization strategy, e.g., biomineralization, for commonly used hydrogel scaffolds can provide an innovative biomanufacturing platform. The first project is focused on direct fabrication of 3D poly (methyl methacrylate) (PMMA) medical plastic through the positive freeform 3D printing. Despite all existing efforts, without chemical modification or mixing with other printable materials, PMMA is not printable due to its dynamic viscosity and poor self-supporting capability. Moreover, bubble formation during the post-curing process causes significant structural defects, failing to produce high quality PMMA implants. Therefore, in this project, a freeform 3D printing platform followed by the pressurized post-curing process was proposed. An alginate-based supporting matrix was specifically designed and optimized for the freeform 3D printing of MMA precursor ink. The post-treatment method with appropriate temperature and pressure was also developed for PMMA curing in supporting matrix via autoclave reactor. The obtained 3D printed PMMA was almost identical to casted PMMA in terms of microstructures, density, and thermal properties, mechanical performance and biocompatibility. The proposed 3D printing platform with the post-curing method has great potential for a direct and cost-effective fabrication method of patient-specific, complex and functional PMMA implants. The second project is for the development of a functional freeform 3D printing system, fabricating hyaluronic acid (HAc)–Calcium Phosphate (CaP) composite hydrogel scaffolds. Most inorganic-hydrogel composites are printed using composite inks consisting of inorganic particles dispersed in a hydrogel-forming ink prior to 3D printing. This simple mixing approach allows easy control over the loading of inorganic particles but optimizing the printability of the composite inks and print quality often becomes more challenging with increased particle loading. To overcome these limitations, in situ precipitation of CaP coupled with the freeform 3D printing process of hydrogels was proposed to fabricate composite hydrogels. The composite hydrogels demonstrated a significant improvement in mechanical strength, biostability as well as biological performance compared to pure HAc. Moreover, multi-material printing of composites with different CaP contents was achieved by adjusting the ionic concentration of inks. This method greatly accelerates the 3D printing of various functional or hybridized materials with complex geometries via the design and modification of printing materials coupled with in situ post-printing functionalization and hybridization in reactive viscoplastic matrices.